Determinan Pemilihan Kontrasepsi Pasca-Persalinan: Perspektif Psikososial - Rochmawati Rochmawati (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
This study explores the psychosocial determinants influencing postpartum contraception selection through a comprehensive approach. A cross-sectional study was conducted on 120 respondents in Bogor Regency, using purposive sampling via Google Forms. Research instruments included the Knowledge Questionnaire on Postpartum Contraception (KQPC) and Multidimensional Health Locus of Control (MHLC) to analyze factors influencing contraception decisions. Research findings demonstrate that knowledge levels, locus of control, economic status, and education significantly impact contraception method selection. Respondents with high knowledge were more likely to choose modern contraception methods (78.3%), while those with low knowledge preferred traditional methods (45.8%). Logistic regression analysis revealed that contraception knowledge contributed most significantly with an odds ratio of 2.512. The study emphasizes the need for personalized approaches in contraception counseling, considering biological, psychological, social, and economic factors. Key recommendations include developing comprehensive educational programs, professional health training, and designing reproductive health policies responsive to individual needs.